2001
DOI: 10.1039/b007250h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and third order nonlinear optics of a new soluble conjugated porphyrin polymer

Abstract: The synthesis of a new soluble conjugated porphyrin polymer 4 is reported. The MALDI TOF mass spectrum shows the presence of oligomers with up to 13 repeat units and GPC gives a M n of 53 kDa. The electronic absorption spectra of this polymer exhibit an intense Q band at 800 nm in solution and 853 nm in the solid state, demonstrating a high degree of conjugation. Electroabsorption spectroscopy shows that thin ®lms of 4 have lower resonant third order NLO susceptibility than our previous conjugated porphyrin po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 39 publications
2
61
0
Order By: Relevance
“…The domain of the optical limiting properties of porphyrin systems comprising multiply porphyrin rings is still poorly explored but gaining more and more attention with the development of new synthetic strategies for their preparation [20,[26][27][28]. Herein we report some consistent trends in nonlinear optical parameters for structurally correlated dimers and trimers.…”
Section: Dimers and Trimersmentioning
confidence: 70%
“…The domain of the optical limiting properties of porphyrin systems comprising multiply porphyrin rings is still poorly explored but gaining more and more attention with the development of new synthetic strategies for their preparation [20,[26][27][28]. Herein we report some consistent trends in nonlinear optical parameters for structurally correlated dimers and trimers.…”
Section: Dimers and Trimersmentioning
confidence: 70%
“…Anderson and co-workers reported that the microscopic polarizabilities of porphyrins in polymers were three orders of magnitude greater than those of monomeric porphyrins. 112 This report described the largest one-photon, 114 suggesting that the use of coordination polymers in sensors may be a growing application area.…”
Section: Porphyrin Systemsmentioning
confidence: 94%
“…VC117exhibits a strong Soret band in the wavelength range of 400-550 nm with an absorption peak at 467 nm and a moderate Q band in the wavelength range of 620-720 nm with a peak around 682 nm, which are the typical characteristics of ethynyl link based porphyrins. 23 The Soret band of VC117 broadens and also red shifts and the Q band also red shifts and intensifies, as compared to other porphyrins which may be attributed to intramolecular charge transfer (ICT) between the donor and acceptor units. These spectral changes indicate an effective π-elongation through the porphyrin core, octyl thiophene-ethynylene π bridge and ethyl rhodanine and better conjugation for VC117.…”
Section: Photophysical and Electrochemical Propertiesmentioning
confidence: 99%